Benign cystic teratoma of fallopian tube with shadow cell differentiation – a rare diagnostic entity with review of literature - Konar, Karabi; Singh, Shivani; Chakrabarti, Nirmalya (International Journal of Research in Medical Sciences, 2017)
A 26 year old gravida 2 para 1 presented to obstetrics department at full term with an unremarkable USG. LSCS was performed for CPD. A fimbrial cyst was discovered intra operatively and excised and sent to us for histopathological examination which showed derivatives of all 3 germ cell layers with presence of shadow cells surrounded by basaloid cells and giant cell reaction. Objective was to report a case of mature cystic teratoma of Fallopian tube with shadow cell differentiation.